Biofertilizers enhance land-use efficiency in intercropping across crop mixtures and spatial arrangements - Pérez-Bernal, Santiago; Sekar, Jegan; Prabavathy, Vaiyapuri Ramalingam; Mathimaran, Natarajan; Thimmegowda, Matadadoddi Nanjundegowda; Bagyaraj, Davis Joseph; Kahmen, Ansgar (Frontiers in Agronomy, 2025)
Intercropping is a common cropping practice that takes advantage of plant diversity and plant complementarity to increase land-use efficiency. Biofertilizers centered around arbuscular mycorrhizal fungi (AMF) and plant growth promoting rhizobacteria (PGPR) are supplements to mineral fertilizers well-known for their far-reaching beneficial effects on plants such as increased drought resistance and increased yields. This study tested if the combination of intercropping and biofertilizers can enhance land-use efficiency (overyielding) using staple crops from southern India. Specifically, the role of different combinations of plant species (crop mixtures) and spatial arrangements mediating overyielding in intercropping was tested. Biofertilizer inoculation increased yields in both monocropping and intercropping. In intercropping, grain yield improved by an average of 23% over the control, regardless of the crop mixture or spatial arrangement. Positive crop-type-specific mycorrhizal growth responses (MGR) and overyielding across experimental treatments and sites indicate that combining biofertilizers with intercropping significantly enhances land-use efficiency in the semi-arid tropics. These findings have practical implications for improving the productivity of intercropping systems in dryland agricultural systems, particularly under resource-limited conditions.